Lymphatic Vessel Thrombosis in a Patient with Secondary Lymphedema. Issue 5 (May 2019) - Hara, Hisako; Mihara, Makoto; Ohtomo, Rie; Tanaka, Sayuri
Abstract : Summary: Lymphatic thrombosis is rarer than venous thrombosis. This case report describes a patient with secondary lymphedema, who was found to have lymphatic thrombosis during lymphaticovenous anastomosis (LVA). A 51-year-old woman underwent hysterectomy and pelvic lymph node dissection for uterine cancer when she was 48 years old, and lymphedema developed in the left leg soon after the operation. She was diagnosed with lymphedema based on lymphoscintigraphic finding. Preoperative echography showed 2 hypoechoic circles measuring about 0.5 mm in diameter that did not collapse with pressure from the probe, although the veins collapsed with pressure. We diagnosed the 2 hypoechoic circles as lymphatic vessels based on the location and longitudinal continuity. During LVA, we identified 2 parallel white vessels beneath the superficial fascia. After they were cut, white material was extruded. A diagnosis of lymphatic thrombosis was made, and we ligated the lymphatic vessels, closed the wound at this site, and performed LVA at other sites (4 sites in the left and 1 site in the right leg). The postoperative course was uneventful. Histopathological examination showed hyperplasty of fibroblasts and organization in the thrombus. Lymphatic thrombosis is sometimes found in the lymphedema-affected extremities. On retrospective consideration, lymphatic thrombosis can be detected with preoperative echography. Abstract : Supplemental Digital Content is available in the text.